Maternal Western diet during gestation and lactation modifies adult offspring's cognitive and hedonic brain processes, behavior, and metabolism in Yucatan minipigs. Issue 12 (13th June 2018) - Gautier, Yentl; Luneau, Isabelle; Coquery, Nicolas; Meurice, Paul; Malbert, Charles‐Henri; Guerin, Sylvie; Kemp, Bas; Bolhuis, J. Elizabeth; Clouard, Caroline; Le Huërou‐Luron, Isabelle; Blat, Sophie; Val‐Laillet, David
ABSTRACT: This study explores the long‐term effects of exposure to a maternal Western diet (WD) vs. standard diet (SD) in the Yucatan minipig, on the adult progeny at lean status ( n = 32), and then overweight status. We investigated eating behavior, cognitive abilities, brain basal glucose metabolism, dopamine transporter availability, microbiota activity, blood lipids, and glucose tolerance. Although both groups demonstrated similar cognitive abilities in a holeboard test, WD pigs expressed a higher stress level than did SD pigs (immobility, P < 0.05) and lower performance in an alley maze ( P = 0.06). WD pigs demonstrated lower dopamine transporter binding potential in the hippocampus and parahippocampal cortex ( P < 0.05 for both), as well as a trend in putamen ( P =0.07), associated with lower basal brain activity in the prefrontal cortex and nucleus accumbens ( P < 0.05) compared with lean SD pigs. Lean WD pigs demonstrated a lower glucose tolerance than did SD animals (higher glucose peak, P < 0.05) and a tendency to a higher incremental area under the curve of insulin from 0 to 30 minutes after intravenous glucose injection ( P < 0.1). Both groups developed glucose intolerance with overweight, but WD animals were less impacted than SD animals. These results demonstrate that maternal diet shaped the offspring's brain functions and cognitive responses long term, even after being fed a balanced diet from weaning, but behavioral effects were only revealed in WD pigs under anxiogenic situation; however, WD animals seemed to cope better with the obesogenic diet from a metabolic standpoint.—Gautier, Y., Luneau, I., Coquery, N., Meurice, P., Malbert, C.‐H., Guerin, S., Kemp, B., Bolhuis, J. E., Clouard, C., Le Huerou‐Luron, I., Blat, S., Val‐Laillet, D. Maternal Western diet during gestation and lactation modifies adult offspring's cognitive and hedonic brain processes, behavior, and metabolism in Yucatan minipigs. FASEB J. 32, 6478–6494 (2018). www.fasebj.org